Supervisor Emotionally Intelligent Behavior and Employee Creativity. (18th February 2020) - Ivcevic, Zorana; Moeller, Julia; Menges, Jochen; Brackett, Marc
Abstract: In a national study of employees across industries ( N  = 14, 645), we examined the role of supervisor emotionally intelligent behavior for employee opportunity to grow, their affect at work, and creativity/innovation at work. Employees reported on their supervisors' emotionally intelligent behavior (perceiving, using, understanding, and managing emotions), and self‐reported about their job experiences and creativity/innovation at work. Supervisor emotionally intelligent behavior was related to employee affect at work assessed using both open‐ended questions and emotion rating scales. Furthermore, supervisor emotionally intelligent behavior was linked to employee creativity/innovation through its effect on employee opportunity to grow and higher experience of positive affect (supporting a serial mediation model). We discuss the implications of the results for creativity/innovation research and innovation management.